Investigation of the Effects of Different Plyometric Training Protocols on Punching Force and Muscle Performance in Male Boxers - Söyler Mehmet; Gürkan Alper Cenk; Kayantaş İdris; Serhat Aydın; Baykal Karataş; Meriç Eraslan; Musa Şahin; Hamza Küçük; Badau Adela; Badau Dana (Applied Sciences, 2025)
This study examines the effects of two plyometric training interventions over an eight-week preparatory period on straight punch impact force, cardiovascular fitness, and muscle strength in national-level boxers. Twenty male professional boxers participated voluntarily, with an average age of 22.64 ± 3.12 years and an average training experience of 5.11 ± 0.88 years. Their mean body weight and height were 70.20 ± 10.13 kg and 184.28 ± 5.38 cm, respectively. The participants were randomly assigned to two groups. Group 1, the Plyometric Stair Jump group, consisted of ten male boxers, while Group 2, the Plyometric Reaction Box Jump group, also included ten male boxers. To assess maximum punching velocity (PVmax), an accelerometer was embedded within the boxing glove, capturing data during three maximal-speed jabs with each arm to evaluate both rear-arm (RA) and lead-arm (LA) punches. Upper-body strength was assessed using a one-repetition maximum (1RM) bench press (BP) test, while maximum velocity at various percentages of 1RM was recorded via a linear encoder. Significant correlations were observed between the right arm punch velocity maximum (RA PVmax) and the bench press velocity at all submaximal intensities in both intervention groups (p < 0.05). However, no correlation was found between left arm punch velocity maximum (LA PVmax) and bench press velocity at any intensity within the Plyometric Reaction Jump (PRJ) group. Conversely, in the Plyometric Stair Jump (PSJ) group, a velocity at 80% of 1RM was the sole significant predictor of RA PVmax at submaximal bench press intensities. Adjusting for the strength-to-weight ratio significantly influenced the predictive values in intergroup comparisons (p < 0.005). These findings suggest that high-load bench press exercises (e.g., at 80% 1RM) may serve as reliable predictors of performance in specific boxing movements. However, since no significant relationship was observed with LA PVmax in this study, further research is warranted to identify exercises and intensities that may explain left arm punch velocity.
Keywords: combat sports; performance; jump; punch speed; high performance; rear arm; lead arm